2020
DOI: 10.3389/fmars.2020.00198
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Intestinal Inflammatory Cytokines and Tight Junction Proteins of Turbot (Scophthalmus maximus L.) During the Development and Recovery of Enteritis Induced by Dietary β-Conglycinin

Abstract: Zheng et al. Dynamics Characterization of Turbot Enteritis the tenth week. Collectively, dietary 8% 7S could induce the serious enteritis of turbot in 3 weeks and the mitigation progress could be observed when turbot are fed with FM diet. The intestinal inflammatory cytokines and tight junction proteins showed different responses during the development and recovery of enteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…For example, proinflammatory cytokines, such as IL-1β, IL-8, and IFN-γ, were linked to reduced tight junction protein gene expression. 67 TNF-α is known to play dual roles in inflamed microenvironments of IECs, leading to barrier defects on the one hand, yet contributing to wound healing on the other hand. 68 Mechanistically, we could also describe how the response on tight junction proteins elicited by AOH and ATX-II ( Figure 8 ) could be modulated by co-incubation with CH-22, indicating an involvement of the AhR pathway in these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, proinflammatory cytokines, such as IL-1β, IL-8, and IFN-γ, were linked to reduced tight junction protein gene expression. 67 TNF-α is known to play dual roles in inflamed microenvironments of IECs, leading to barrier defects on the one hand, yet contributing to wound healing on the other hand. 68 Mechanistically, we could also describe how the response on tight junction proteins elicited by AOH and ATX-II ( Figure 8 ) could be modulated by co-incubation with CH-22, indicating an involvement of the AhR pathway in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bidirectional effectivity on epithelial barrier function was previously reported for both cytokines investigated in this study, among others. For example, proinflammatory cytokines, such as IL-1β, IL-8, and IFN-γ, were linked to reduced tight junction protein gene expression . TNF-α is known to play dual roles in inflamed microenvironments of IECs, leading to barrier defects on the one hand, yet contributing to wound healing on the other hand .…”
Section: Discussionmentioning
confidence: 99%
“…D-lactic acid is a metabolic product of bacteria mainly found in the intestinal mucosa ( Liu et al., 2020b ). A complete intestinal mucosal barrier can prevent DAO and D-LA from entering the blood circulation ( Zheng et al., 2020 ). Therefore, the intestinal barrier function can be assessed indirectly by assessing plasma DAO activity and D-LA concentration ( Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, SM contains some anti-nutritional factors including trypsin inhibitors, antigen proteins, lectins, tannins, saponins and alkaloids ( 1 3 ). Previous studies on Atlantic salmon ( Salmo salar ) ( 4 , 5 ), zebrafish ( Danio rerio ) ( 6 ), rice field eel ( Monopterus albus ) ( 7 ), Japanese seabass ( Lateolabrax maculatus ) ( 8 ), largemouth bass ( 9 ) and Mirror carp ( Cyprinus carpio ) ( 10 ) have shown that, excessive use of SM in feed can cause intestinal inflammation and injury, intestinal digestion and absorption dysfunction, and ultimately reduce growth performance ( 11 , 12 ), especially in carnivorous fish.…”
Section: Introductionmentioning
confidence: 99%